Impact of an online mindfulness-based program on wellbeing and trait mindfulness for research postgraduate students: a randomized-controlled trial - Jia-Qi Xu; Yee-Man Jennifer Tang; Hoi Ying Katherine Chen (BMC Psychology)
Abstract Objectives Pursuing a research postgraduate (RPg) degree is a major life event and could be stressful. The current study aims to explore the effectiveness of an online eight-week mindfulness-based intervention on improving wellbeing and alleviating illbeing among a group of RPg students using a randomized waitlist-controlled design. Methods A total of 88 RPg students, either studying in Hong Kong or Macau, were recruited (43 were randomized into the immediate intervention group; 67 females; mean age = 27.7; SD = 4.60). The “Finding Peace in a Frantic World” was adopted as the mindfulness-based program. Linear mixed models were applied to test the effects of the intervention on trait mindfulness, compassion, wellbeing related measures (i.e., subjective wellbeing, resilience, wellbeing literacy) and illbeing related measures (i.e., emotional and sleeping disturbances), while controlling for the effects of age and gender. The intervention group was also assessed at two-month follow-up to evaluate the sustained effects. Results The results revealed that participants from the intervention group showed increased resilience (b = 0.88, p = .012), wellbeing literacy (b = 2.52, p = .04), trait mindfulness (b = 5.16, p = .006), and decreased emotional disturbances (b=-8.24, p = .015), while there were no changes in subjective wellbeing, sleeping quality, and self-compassion or compassion towards others compared to the waitlist controls. Positive effects were sustained after two months in the intervention group. Conclusions This study provides evidence for online mindfulness training in alleviating RPg students’ emotional disturbance and supporting their resilience and wellbeing literacy. Registration The study was retrospectively registered with the ISRCTN Registry on 11/11/2022 (registration number: ISRCTN18262344).